Working the Edges of the Nineteenth‐Century British Empire. Issue 5 (May 2016) - Watson, Tim
Abstract: In this essay, I pay attention to some of the edges, margins, and middle spaces of the nineteenth‐century empire and suggest that the movements, people, and cultural practices of the edges of empire were crucially important for the construction of empire itself. I tell the stories of two imperial middlemen, people who worked from the edges of the nineteenth‐century British imperial world, in Jamaica, New Zealand/Aotearoa, and Britain, who worked with the constraints in which their economic, racial, and national situations placed them and tried to generate cultural capital to offset their marginal status. Hosting musical soirees in Kingston, Jamaica and performing ethnographic masquerades in the provincial lecture halls and theatres of Britain, Louis Celeste Lecesne and Barnet Burns, the subjects of this article, put a human face to the abstract logic of speculative finance and demonstrate the importance of cultural practice to the institutions of empire.